As metamorfoses do nome: história, política e recombinações identitárias entre os Tupi Guarani - Bertapeli, Vladimir [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The study that follows is about the ethnonym Tupi Guarani and its constitution by an eponymous ethnic group that forms the aldeia Tabacu Reko Ypy, located in the Terra Indígena Piaçaguera, in the São Paulo state coast. According to the information obtained in the field, these natives claim that their identity is grounded in the mistura, ie in marriages that have been taking place over time for their Tupi and Guarani ancestors. The consulted historical and anthropological sources confirm that relations between the remnants of the Tupi groups - who inhabited the ancient aldeamento São João Baptista de Peruibe, Itariri and its surroundings, respectively located on the coast and Vale do Ribeira - and Guarani - Apapocúva, Tañyguá and Oguauíva - began in the late nineteenth century and early twentieth. The story also shows that the ancestors of Tupi Guarani had various names throughout history. Thus, they were called índios civilizados, mansos, aldeados, Carijó, aculturados, etc. Thus, these terms contrasted with those assigned to Tapuia, which were also dubbed selvagens, bravos, botocudos and autênticos. The story also points out that these designations also served both to establish alliances between indigenous and non-indigenous but also served to engender conflict. Moreover, these terms contributed to the conduct of an indigenous law that ranged from the amenity and repression. Moreover, researchers and other authorities considered that the descendants of the Tupi and Guarani who lived in the woods or around the coastal cities and the countryside of São Paulo were just fragments or imitations of ancient natives who inhabited the coast. So this brought to such people a lot of problems, both political and social. Thus, this research deals with this historical process, political and social constitution of the ethnonym Tupi Guarani. We will ...

O estudo que segue versa sobre o etnônimo Tupi Guarani e sua constituição por um grupo étnico homônimo que forma a aldeia Tabaçu Rekó Ypy, localizada na Terra Indígena Piaçaguera, no litoral do Estado de São Paulo. Conforme as informações obtidas em campo, estes indígenas alegam que sua identidade está embasada na mistura, ou seja, nos casamentos que foram se realizando ao longo do tempo pelos seus antepassados Tupi e Guarani. As fontes históricas e antropológicas consultadas confirmam que as relações entre os remanescentes dos grupos Tupi - que habitavam os antigos aldeamentos do São João Batista de Peruíbe, Itariri e seus arredores, respectivamente localizados no litoral paulista e Vale do Ribeira - e os Guarani - Apapocúva, Tañyguá e Oguauíva -começaram após a chegada destes últimos nas décadas finais do século XIX e início do XX. A história ainda evidencia que os antepassados dos Tupi Guarani receberam várias designações ao longo da história. Assim, eles foram chamados de índios civilizados, mansos, aldeados, Carijó, aculturados, etc. Logo, esses termos contrastavam com aqueles atribuídos aos Tapuia, que foram apelidados de selvagens, bravos, botocudos e autênticos. Consta nas fontes históricas que estas denominações serviram tanto para o estabelecimento de alianças entre indígenas e não indígenas como também convieram para engendrar conflitos. Ademais, estes termos contribuíram para a condução de uma legislação indigenista que oscilava entre a amenidade e a repressão. De mais a mais, pesquisadores e demais autoridades consideravam que os descendentes dos Tupi e Guarani que viviam pelas matas ou nos arredores das cidades litorâneas e pelo interior de São Paulo não passavam de fragmentos ou arremedos dos antigos nativos que habitavam a costa. Logo, isto trouxe para tais povos uma série de problemas, tanto políticos...
Keywords: História; Identidade; Indios - Aspectos políticos; Nativos; History